Influência do teor de Hf em filmes finos de Zr e ZrN depositados por magnetron sputtering - Santos, Ikaro Arthur Dantas (2018)
Zr-Hf-N and Zr-Hf thin films were deposited by reactive magnetron sputtering in order to verify the influence of small hafnium contents that are present as contaminants on zirconium deposition targets. For this purpose different hafnium contents in the films were intentionally added by varying the deposition power. The samples were characterized by X-ray diffraction (XRD), dispersive energy X-ray spectroscopy (EDS), Rutherford backscattering spectroscopy (RBS) and nanohardness analyzes. The ZrHfN thin films were deposited and had a concentration of at% Hf of 0.49; 0.56; 0.80; 1.87 and 2.70. The deposited Zr-Hf alloys exhibited hafnium contents at up to 1.21%; 1.24; 4.35; 7.94 and 11.49. The crystalline phase obtained for the nitride films had a cubic face centered structure (FCC) and was not modified by the increase in hafnium content. The alloys presented amorphous with some crystalline regions of hexagonal structure. The hardness values ranged from 21.4 to 25.1 GPa for nitrides and from 6.1 to 8.4 GPa for zirconium alloys.